Application of Goal Programming Model for Optimization Tofu Production Planning - Juli Antasari Br Sinaga; Rajainal Saragih; Lilis Lilis; Yoel Octobe Purba; Reagen Surbakti Saragih (UIN Sumatera Utara, 2025)
Previous studies on production planning in food SMEs have largely focused on single-objective optimization and often lack explicit optimality benchmarks under real resource constraints. This study addresses this gap by developing a multi-objective production planning model using Goal Programming for a small-scale tofu enterprise. The proposed model simultaneously considers profit targets, demand fulfillment, raw material availability, and labor hour limitations. The novelty of this research lies in the use of deviation-based optimality benchmarks and its practical implementation using POM-QM for Windows. Model validation is conducted through a real case study, resulting in an optimal production mix of 724 units of white tofu, 568 units of fried tofu, and 517 units of yellow tofu, achieving a monthly profit of IDR 73.90 million with zero positive deviation from the profit target. Resource utilization remains within capacity limits, as indicated by negative deviations in raw material usage and labor hours. These results demonstrate that Goal Programming is an effective and practical decision-support tool for resource-constrained food SMEs.